Mystery swine disease in the Netherlands: The isolation of Lelystad virus - Wensvoort, G.; Terpstra, C.; Pol, J.M.A.; ter Laak, E.A.; Bloemraad, M.; de Kluyver, E.P.; Kragten, C.; van Buiten, L.; den Besten, A.; Wagenaar, F.; Broekhuijsen, J.M.; Moonen, P.L.J.M.; et al. (Journal of Economic Literature, 1991)
In early 1991, the Dutch pig-industry was struck by the so-called mystery swine disease. Large-scale laboratory investigations were undertaken to search for the etiological agent. We focused on isolating viruses and mycoplasmas, and we tested paired sera of affected sows for antibodies against ten known pig viruses. The mycoplasmas M. hyosynoviae, M. hyopneumoniae, and Acholeplasma laidlawii, and the viruses encephalomyocarditis virus and porcine enterovirus types 2 and 7 were isolated from individual pigs. An unknown agent, however, was isolated from 16 of 20 piglets and from 41 of 63 sows. This agent was characterised as a virus and designated Lelystad virus. No relationship between this virus and other viruses has yet been established. Of 165 sows reportedly afflicted by the disease, 123 (75 per cent) seroconverted to Lelystad virus, whereas less than 10 per cent seroconverted to any of the other virus isolates or to the known viral pathogens. Antibodies directed against Lelystad virus were also found in pigs with mystery swine disease in England, Germany, and in the United States. We conclude that infection with Lelystad virus is the likely cause of mystery swine disease.